Theoretical Prediction of Selectivity in Solvent Extraction of La(Iii) and Ce(Iii) from Aqueous Solutions Using β-diketones as Extractants and Kerosene and Two Imidazolium-Based Ionic Liquids as Diluents Via Quantum Chemistry and Cosmo-Rs Calculations - Pizarro-Konczak, J; Ortiz-Calderon, C; Romero-Figueroa, J; Quijada-Maldonado, E; Olea-Chandia, F; Quintriqueo-Cid, A (Elsevier B.V., 2021)
This study proposes a theoretical method based on DFT and COSMO-RS calculations to predict selectivity in the solvent extraction (SX) of lanthanum(III) and cerium(III), by using β-diketones as the extractant and kerosene or imidazolium-based ionic liquids (ILs) as the diluent. To calculate the selectivity, the model requires three important pieces of information: the extraction stoichiometry, the type and structure of the extractant/synergistic agent, and the diluent used in the SX process. Therefore, as the first step, the extraction stoichiometry is determined experimentally. Using these results to perform DFT and COSMO-RS calculations, thermochemical parameters allowed to calculate the selectivity. The results indicate that the theoretical selectivity trends agree closely with the experimental results even when using ILs as diluents, demonstrating the applicability of this method. It is established that the selectivity can be increased by using both β-diketones with bulky functional groups and a synergistic agent. This predictive method has immense potential as a practical tool providing valuable insights into the design of extractants and hydrophobic diluents for the selective recovery of lanthanides in industrial applications. © 2020 Elsevier B.V.